If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2n + -3) = 60 Reorder the terms: 4(-3 + 2n) = 60 (-3 * 4 + 2n * 4) = 60 (-12 + 8n) = 60 Solving -12 + 8n = 60 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 8n = 60 + 12 Combine like terms: -12 + 12 = 0 0 + 8n = 60 + 12 8n = 60 + 12 Combine like terms: 60 + 12 = 72 8n = 72 Divide each side by '8'. n = 9 Simplifying n = 9
| 27=15p+12 | | m+7=-49 | | -4(c-3)-2=2(c-1)+3(c-2) | | 12x-14y+3z=13 | | 4u-10u= | | 5v-4+2+7v= | | 31b-777= | | -8+6x+3x+4= | | 4.4=-6.5h+36.9 | | 58=-22+10x | | -7p+p=-4 | | 2e^2+12e-22= | | -5u+2+5u= | | W+2w+w+w= | | 4x^3-16x+2=0 | | t-2.89=915 | | -8x+2(x+2)=-26 | | -11+-5= | | 7n+5-5n-6= | | -3(2x-10)=-30 | | 4x-5y=-45 | | 4x=2y+10 | | -3n+10+n+9= | | 8x-7y=-63 | | 19=6d+1 | | 3r^27=0 | | 6g+24=72 | | 6x+5-1= | | 81xy-16x=36xy | | 10v-8+5v-6= | | 9x+40+4y+8=180 | | 19p+14=89-6p |